DRESSING AT THE LITURGY: THE EXAMPLE OF THE SERBIAN ORTHODOX CHURCH - Anđelković Bilјana (Bulletin of the Institute of Ethnography SASA, 2022)
This paper discusses the clothing of the Serbian Orthodox Church believers at the end of the twentieth and the beginning of the twenty-first century. The main goal was to determine whether there is a desirable/ideal model of clothing for SOC believers, at the liturgy as well as the type and degree of deviation from it in the daily practice of believers. The paper is based on ethnographic material collected during the last five years in churches and monasteries throughout Serbia using the method of observation, semi-structured questionnaire, informal conversation and the use of information from Orthodox forums and websites.